2002
DOI: 10.1046/j.1529-8027.2002.02028.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel sequence variants in the neurofilament‐light gene in a Japanese population: analysis of Charcot‐Marie‐Tooth disease patients and normal individuals

Abstract: Mutations of the neurofilament-light (NEFL/NF-L) gene were examined in 124 unrelated Japanese patients with Charcot-Marie-Tooth disease (CMT) without known gene mutations, and 248 normal Japanese individuals. A new method, which can detect basepair mismatches with RNase cleavage on agarose gel electrophoresis, coupled with DNA sequencing, identified 8 novel sequence variations in the NF-L gene. In these sequence variants, 5 variants were polymorphisms, including 3 single nucleotide polymorphisms (SNPs), and 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 12 publications
3
63
0
1
Order By: Relevance
“…We believed that this mutation was the underlying cause of the CMT1 phenotype in the FC99 family for the following reasons: cosegregation of the mutation with affected members of the pedigree, no similar mutation in controls (n = 210), well-conserved Pro22 among different species, and the findings of previous reports on the effect of different mutations at the Pro22 site. It seems that codon 22 is one of the mutational hot spots in the NEFL gene because three different Pro22 mutations, including the one found in this study, have been reported (Fabrizi et al 2004;Georgiou et al 2002;Yoshihara et al 2002). Three different families have been reported to have Pro22 mutations: Pro22Ser in a Slovenian family (Georgiou et al 2002) and an Italian family (Fabrizi et al 2004), and Pro22Thr in a Japanese family (Yoshihara et al 2002).…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…We believed that this mutation was the underlying cause of the CMT1 phenotype in the FC99 family for the following reasons: cosegregation of the mutation with affected members of the pedigree, no similar mutation in controls (n = 210), well-conserved Pro22 among different species, and the findings of previous reports on the effect of different mutations at the Pro22 site. It seems that codon 22 is one of the mutational hot spots in the NEFL gene because three different Pro22 mutations, including the one found in this study, have been reported (Fabrizi et al 2004;Georgiou et al 2002;Yoshihara et al 2002). Three different families have been reported to have Pro22 mutations: Pro22Ser in a Slovenian family (Georgiou et al 2002) and an Italian family (Fabrizi et al 2004), and Pro22Thr in a Japanese family (Yoshihara et al 2002).…”
Section: Discussionmentioning
confidence: 48%
“…Histopathological features were only described in a Pro22Ser patient in an Italian family and featured giant axons with neurofilament accumulation (Fabrizi et al 2004). However, the Japanese family with the Pro22Thr mutation was reported to have the CMT1 phenotype based on clinical and electrophysiological features (Yoshihara et al 2002). Moreover, the FC99 family with Pro22Arg mutation also showed a CMT1 neuropathy with onion bulb formations in this study.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations